Docking study on anti-HIV-1 activity of secondary metabolites from Zingiberaceae plants - Muhammad Sulaiman Zubair; Saipul Maulana; Agustinus Widodo; Alwiyah Mukaddas; Ramadanil Pitopang (Wolters Kluwer Medknow Publications, 2020)
Introduction: Human immunodeficiency virus type-1 (HIV-1) that causes acquired immunodeficiency syndrome (AIDS) has become a worldwide health problem today. There are approximately 30 anti-HIV-1 drugs that have been used in the treatment of AIDS. However, effective anti HIV-1 agents with less side affect and high inhibition potency are still in demand. Objective: The objective of this study was to identify the potential compounds from Zingiberaceae plants that might be active as anti-HIV-1 by molecular docking. Materials and Methods: Molecular docking simulation was performed by using AutoDock 4.2 on Linux operation system. Docking protocol was validated by using root mean square deviation (RMSD) value using redocking and cross-docking methods. The reported metabolites from Zingiberaceae plants were docked on HIV-1 protease, integrase, and reverse transcriptase protein enzymes. Results: The docking result showed that the genera of Zingiber, Etlingera, Alpinia, Hedychium, and Boesenbergia have potential metabolites that inhibit HIV protease, integrase, and reverse transcriptase enzymes by possessing lower docking energy than native ligand of amprenavir, raltegravir, and nevirapine. Among the metabolites, noralpindenoside B and alpindenoside A from Alpinia densespicata inhibited protease enzymes with the lowest docking energy of -18.02 and -17.90 kcal/mol, respectively. Meanwhile, panduratin E from Boesenbergia pandurata Roxb. and 5α,8α-epidioxyergosta-6,22-dien-3β-ol from Etlingera elatior showed the lowest docking energy on integrase protein with docking energy of -11.97 and -11.41 kcal/mol, respectively. Pahangensin A from Alpinia pahangensis Ridley showed the lowest docking energy on reverse transcriptase enzyme with docking energy of -13.76 kcal/mol. Conclusion: The docking molecular study has identified the possible potential compounds from Zingiberaceae plants that might be used for anti-HIV-1 treatment. So, this study suggested further isolation and purification of the predicted compounds.